Pemberian Terapi Hot-Pack Elektrik Menurunkan Skala Nyeri Dismenore Remaja Putri dengan Pendekatan Teori Kognitif - Dhinda Salsabil Maharani; Sumirah Budi Pertami; Nurul Pujiastuti; Sulastyawati Sulastyawati (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2024)
During menstruation, young women can experience problems, one of which is dysmenorrhea. Knowing the effect of giving electric hot-pack therapy to reducing dysmenorrhea pain scale with a cognitive theory approach. Research design using Quasy Experiment. The sampling technique is purposive sampling with 44 respondents. Data processing uses the Wilcoxon and Man Withney tests. The treatment group showed that most of the results (72.7%) were mild pain scales and the control group mostly (72.7%) were moderate pain scales. The Wilcoxon test results are Sig. (2-tailed) = 0.000, which means that there is a significant effect on the pain scale before and after giving electric hot-pack therapy to young women. The results of the man withney test are Sig. (2-tailed) = 0.005, which means that there is a significant difference in the pain scale between the treatment group and the control group. Giving electric hot-pack therapy to young women who experience dysmenorrhea can reduce pain and provide a sense of comfort.